(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the current conditions of macroeconomic instability, small and medium-sized businesses face increased risks of investment activities. Fluctuations in exchange rates, changes in the discount rate and a decrease in the level of liquidity in the financial sector complicate the attraction and effective use of investment resources. Therefore, it is relevant to study financial instruments as key determinants of the stability of investment activities that contribute to the adaptation of enterprises to a volatile environment. Purpose. The purpose of the study is to determine the role of financial instruments in ensuring the stability of investment activities of small and medium-sized businesses in conditions of macroeconomic volatility, to determine the mechanisms of their adaptation to an unstable environment and to substantiate risk minimization strategies. Methods. The methodological basis of the study is a systematic approach, which involves the use of specialized analysis methods to assess the impact of financial instruments on the investment stability of enterprises. Content analysis was used to identify the dynamics of macroeconomic indicators that affect the financial mechanisms of small and medium-sized businesses. Abstract and comparative methods, as well as the method of logical generalization, were used to formulate conclusions regarding the role of financial instruments in stabilizing the investment activities of enterprises in conditions of macroeconomic volatility. Results. The article considers the impact of macroeconomic volatility on the investment activities of small and medium-sized businesses. The mechanisms for using financial instruments that provide for hedging currency risks and insurance of investments to ensure the long-term financial stability of business entities are analyzed. The impact of monetary policy on the availability of financial resources for small businesses is studied. It is proven that the integration of modern financial technologies contributes to increasing the investment stability of enterprises. The effectiveness of combined approaches to financial risk management in an unstable economic environment is assessed. Conclusions. The dynamic transformation of the economic environment necessitates a multi-vector analysis of investment risks, which results in the need to integrate multi-level financial forecasting algorithms and use complex capital management models. This approach requires the use of adaptive financial mechanisms that combine strategic diversification of capital sources and optimization of risk management. At the same time, the financial stability of small and medium-sized businesses is directly determined by the level of effectiveness of hedging currency and interest rate risks, which, in turn, depends on the depth of integration of financial technologies and the level of availability of insurance mechanisms.